2017
DOI: 10.1073/pnas.1700978114
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Shp2 directs normal embryo implantation via facilitating the ERα tyrosine phosphorylation by the Src kinase

Abstract: Estrogen and progesterone coupled with locally produced signaling molecules are essential for embryo implantation. However, the hierarchical landscape of the molecular pathways that governs this process remains largely unexplored. Here we show that the protein tyrosine phosphatase Shp2, a positive transducer of RTK signaling, is predominately localized in the nuclei in the periimplantation mouse uterus. Uterine-specific deletion of Shp2 exhibits reduced progesterone receptor (PR) expression and progesterone re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 31 publications
1
62
0
Order By: Relevance
“…PR antagonist RU486 injection in the peri‐implantation period hampers uterine PDS and embryo implantation in wild‐type (WT) mice . According to the previous literature, implantation failure occurs in all types of mice with impaired uterine PDS . PR has two isoforms, PR‐A and PR‐B.…”
Section: P4‐pr Signaling Controls Uterine Pds and Receptivitymentioning
confidence: 99%
See 1 more Smart Citation
“…PR antagonist RU486 injection in the peri‐implantation period hampers uterine PDS and embryo implantation in wild‐type (WT) mice . According to the previous literature, implantation failure occurs in all types of mice with impaired uterine PDS . PR has two isoforms, PR‐A and PR‐B.…”
Section: P4‐pr Signaling Controls Uterine Pds and Receptivitymentioning
confidence: 99%
“…Intriguingly, the treatment with ER antagonist ICI‐182780 can rescue not only this hormonal signaling imbalance but also implantation failure . Protein tyrosine phosphatase SHP2, classic cytoplasmic protein, is present mainly in the nucleus of endometrial cells during implantation, and nuclear SHP2 enhances SRC kinase‐mediated ERα tyrosine phosphorylation, assists combining ERα with PR promoter, and proceeds the ERα transcription activity in the peri‐implantation period (Figure ).…”
Section: Appropriate Balance Between E2 and P4 Is Necessary For Uterimentioning
confidence: 99%
“…Successful implantation requires the development of embryo to implantation-competent blastocyst and the synchronized transformation of uteri into a receptive stage [1-3]. Previous study has confirmed that Hmgn2 could play an important role in preimplantation embryonic development [12], but its biological function during embryo implantation remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have demonstrated that Src interacts with the estrogen receptor even in other cells such as the uterine cells and human breast cancer cells. Indeed, in the nuclei of uterine cells, active Src can phosphorylates estrogen receptor α (ERα) and enhances its transcriptional activity due to the activity of SHP2 (Src-Homology Protein2) [63]. SHP2, a protein encoded by the gene PTPN11, is generally located in the cytoplasm, but it is also known to translocate in the nucleus when DNA damage occurs [64].…”
Section: Src and Estrogen Receptormentioning
confidence: 99%
“…SHP2, a protein encoded by the gene PTPN11, is generally located in the cytoplasm, but it is also known to translocate in the nucleus when DNA damage occurs [64]. SHP2 enhances Src tyrosine kinase activity by removing its inhibitory phosphorylation and Src, in turn, phosphorylates ERα, thus allowing its binding to the progesterone receptor promoter and driving its transcription [63].…”
Section: Src and Estrogen Receptormentioning
confidence: 99%